The Integration of TPM in SS-DMAIC Framework to Reduce Production Losses and Enhance Process Performance: a Case Study - Chukwuebuka Martinjoe U-Dominic; Ifeyinwa Juliet Orji; Uchendu Onwusoronye Onwurah; Nwufo Maduka Augustine (Journal Majelis Paspama, 2025)
The primary cause of production system losses is widely recognised to be unplanned stoppages and breakdowns, as idle machines waste time and lower output and throughput. Many firms have undergone a paradigm shift from traditional methods to more sophisticated process improvement strategies to address the dynamic and ever-changing production constraints. To lower production downtimes and other process-related issues, an integrated improvement approach of TPM-SS-DMAIC was used in this study. The new suggested approach was validated in the cable manufacturing industry. The goals of the study were achieved in terms of increased worker knowledge, better quality, and fewer unplanned stoppages and breakdowns. Standard operating procedures were updated in response to suggestions for ways to reduce needless stoppages in extrusion line operations. Furthermore, following the process change, the overall equipment effectiveness (OEE) increased from 58% to 63%, indicating a noteworthy level of improvement.